Study of Student Islamic Financial Literacy Levels At Islamic College - Rafidah; Muhammad Subhan; Amrullah (Universitas Islam Negeri Alauddin Makassar, 2022)
The low literacy of Islamic finance in several semester VI students of the Faculty of Economics and Business, UIN Sulthan Thaha Saifuddin Jambi really needs attention because it is in the 50% - 59% category. in understanding mudharabah contracts, Islamic insurance related to Islamic insurance products, benefits and risk concepts, as well as understanding Islamic investment. This will affect Islamic financial inclusion and have an impact on the development of Islamic finance in the long term. This study used a quantitative descriptive method, a population of 577 people and a sample of 100 people. Data collection was carried out by distributing research questionnaires to semester VI students of the Faculty of Economics and Business, UIN Sulthan Thaha Saifuddin Jambi, while the results of the research indicated financial literacy for aspects of basic Islamic finance knowledge, namely 81%, indicating a good understanding of the basics of Islamic finance. However, for the aspect of understanding about savings and loans, Islamic insurance, Islamic investment is still in the medium category because it is still at 68.8% - 77.8%. This shows that there is still a great need to increase knowledge and understanding of Islamic financial institutions in this case regarding Islamic banking, Islamic insurance and Islamic capital markets. Efforts to increase Islamic financial literacy with several activities such as: Socialization of Islamic Banking and Islamic insurance, holding workshops or seminars, competitions on Islamic Financial Institutions.